The Effect of Life Skills-Based Group Counseling on Stress in Female Adolescents: A Randomized Controlled Trial - Nahid Safabakhsh; Taraneh Emamghooli Khooshehchin; Leila Rastegari; Saeedeh Zenoozian (Zanjan University of Medical Sciences and Health Services, 2023)
Background: Adolescence is considered one of the most important periods in the life of any human being. In most cases, adolescents suffer from fear, anxiety, and stress during this period, and how to pass through this period considerably affects their mental and physical health. Objectives: This study was conducted to investigate the effect of life skills-based group counseling on stress in female adolescents in the city of Zanjan. Methods: The present study is a randomized controlled trial with parallel groups. Sixty four female adolescents under the coverage of health centers in the city of Zanjan in 2019 were initially divided into two intervention (n=32) and control groups (n=32) by blocked random sampling method. In the intervention group, eight sessions of life skills-based group counseling were conducted once a week for 90 minutes. Data were collected using Cohen's Perceived Stress Scale (PSS) and were analyzed using the Mann-Whitney U and repeated measurements tests in SPSS 18 software. Results: The results indicated no significant difference between the two intervention (35.06 ± 9.56) and control (29.94±9.16) groups before the intervention (p=0.253). The mean stress score two months after the intervention was significantly lower in the intervention group (29.94 ± 7.59) than in the control group (37.17±9.16) (p<0.043). Conclusion: Based on the study results, life skills-based group counseling can reduce stress in female adolescents. Therefore, it is recommended to use this method as a part of health system care for female adolescents in schools and comprehensive health centers.